UPSKILL MATH PLUS

Learn Mathematics through our AI based learning portal with the support of our Academic Experts!

Learn moreThe square root of a polynomial using the factorization method can be used only if the degrees of the polynomial are smaller.

The procedure to find the square root of a polynomial using the factorization method is given by:

**Step 1**: If the given polynomial is a quadratic equation, factorize them by splitting the middle terms or factorize them using algebraic identities.

**Step 2**: Take the square root of the factorized terms.

Let us understand how to find the square root of a polynomial by the factorization method in the following examples.

Example:

**1**. Find the square root of \(144(x - a)^2(x -b)^{10}\).

**Solution**:

\(\sqrt{144(x - a)^2(x -b)^{10}} = 12|(x - a)(x -b)^5|\)

**2**. Find the square root of \((5x - 2y)^2 + 40xy\).

**Solution**:

\(\sqrt{(5x - 2y)^2 + 40xy} = \sqrt{25x^2 - 20xy + 4y^2 + 40xy}\)

\(= \sqrt{25x^2 + 20xy + 4y^2}\)

\(= \sqrt{(5x)^2 + 2(5x)(2y) + (2y)^2}\)

\(= \sqrt{(5x + 2y)^2}\)

\(= |(5x + 2y)|\)

**3**. Find the square root of \((6x^2 + 7x - 5)(2x^2 + 9x - 5)(3x^2 + 20x + 25)\)

**Solution**:

Let us factorize the polynomials.

\(6x^2 + 7x - 5 = 6x^2 + 10x - 3x - 5\)

\(= 2x(3x + 5) - 1(3x + 5)\)

\(= (3x + 5)(2x - 1)\)

\(2x^2 + 9x - 5 = 2x^2 + 10x - x - 5\)

\(= 2x(x + 5) - 1(x + 5)\)

\(= (2x - 1)(x + 5)\)

\(3x^2 + 20x + 25 = 3x^2 + 15x + 5x + 25\)

\(= 3x(x + 5) + 5(x + 5)\)

\(= (x + 5)(3x + 5)\)

\(\sqrt{(6x^2 + 7x - 5)(2x^2 + 9x - 5)(3x^2 + 20x + 25)} = \sqrt{(3x + 5)(2x - 1)(2x - 1)(x + 5)(x + 5)(3x + 5)}\)

\(= \sqrt{(3x + 5)^2(2x - 1)^2(x + 5)^2}\)

\(= (3x + 5)(2x - 1)(x + 5)\)